Cash Management : (Frank J. Fabozzi associtates, 2000)
Cash, as opposed to more rewarding but riskier assets, such as stocks or bonds, is preferable for meeting large, short-term liabilities that are well defined and predictable. Holding cash is also the only sensible investment choice for meeting uncertain (contingent) liabilities that arise in an emergency. The range of cash management alternatives is sufficiently wide and complicated to warrant careful planning when deciding on which specific cash vehicles to hold. The general principles of modern portfolio management can and should be applied to professional cash management